On the effect of fumed silica particles on the structure, properties and application of PVDF membranes - Mavukkandy, M.O. (Elsevier B.V., 2017)
This study explored the impact of hydrophobic fumed silica (FS) particles as an inorganic additive in the preparation of polyvinylidenefluoride (PVDF) membranes using the phase inversion technique. PVDF membranes were prepared by varying the percentage of FS additive (0–5 wt) in the dope solution. Hansen solubility parameters (HSPs) were calculated in order to assess the affinity/compatibility of FS additive with the PVDF and dimethyl acetamide (DMAc) system. The thermodynamic and kinetic aspects of the membrane formation were studied. HSPs demonstrated good compatibility of the PVDF, DMAc and FS. Results showed that the resulting membrane morphology was a trade-off between the thermodynamic enhancement and kinetic hindrance caused by the addition of FS. The prepared membranes were applied for the filtration of the raw wastewater. Although PVDF-FS blend membrane showed much higher flux, their fouling propensity was also high due to their increased hydrophobicity. This study revealed the important role of FS as an additive and highlighted the role of this additive in forming membranes with less tortuosity and narrower pore size distribution. © 2017 Elsevier B.V.